Online Gamma Radiation Monitoring Using Few-Mode Polymer CYTOP Fiber Bragg Gratings - Chapalo, Ivan; Gusarov, Andreï I.; Ioannou, Andreas; Posporis, Andreas; Chah, Karima; Nan, Ying-Gang; Kalli, Kyriacos; Megret, Patrice (My University, 2022)
We investigated the gamma radiation response of fiber Bragg gratings (FBGs) inscribed in a few-mode polymer optical fiber. The fiber had a graded-index CYTOP core of 20 µm and XYLEX overclad of 250 µm in diameter. Four FBGs were exposed to gamma radiation during four irradiation sessions at a 5.3 kGy/h dose rate. The FBGs showed a linear Bragg wavelength shift with the received dose with a mean sensitivity of -3.95 pm/kGy at 43 °C. The increased temperature provides a rise in the sensitivity: it reached -10.6 pm/kGy at 58 °C. After irradiation, the FBGs showed partial recovery, which increased with the received dose. Furthermore, the FBG's reflection power decreased with the dose. This attenuation is mainly due to insertion losses caused by the radiation induced attenuation in the CYTOP fiber. Linear response to the received dose makes CYTOP FBGs attractive for gamma radiation dosimetry. However, temperature dependence of the sensitivity should be compensated in practical applications.
Keywords: polymer optical fiber; gamma radiation dosimetry; fiber Bragg gratings; gamma radiation; CYTOP; polymer perfluorinated fiber